Mengembangkan Bisnis Desain Grafis - Irwan Harnoko (Humaniora, 2011)
Developing graphic design business needs promotion materials, some of them are newsletter, business card, Credit Line, and protofolio. Article explores the strategy of making newsletter, how to make business card to be professional, how to get the credit line, and how to make a portofolio, and what media that is able to clearly clarify the portofolio. It is concluded that people need extra ordinary creativity to achieve a successful in graphic design business.